(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article describes the nature of the assessment and its categorical signs, the uniqueness of the status of the assessment category, it is determined based on the relationship of human thinking with objective reality, the denotation of units naming things and events is evaluated not only ontologically, but also in relation to certain characteristics.